PROCESSING INDUSTRY INVESTMENT FEASIBILITY ANALYSIS TAPIOCA FLOUR IN ACEH BESAR DISTRICT - Hasnawi; Ahmad Humam Hamid; Fajri (CV. Radja Publika, 2023)
The development of agro-industry still has several obstacles in its implementation. This is wrongly caused by the characteristics of agro-industry which have a relationship from upstream to downstream, there must be guaranteed production from upstream so that there will be continuity of production. In addition, human resources are not yet qualified and equipment is still relatively simple, one of which is processing cassava into tapioca flour in Aceh Besar District. The purpose of this study is to analyze the feasibility of investing in the tapioca flour industry in Aceh Besar District from a financial perspective. The feasibility analysis approach method on the financial aspect is carried out quantitatively. Analysis of the financial aspect for investment in the tapioca flour processing industry can be assessed with four criteria, namely: NPV (Net Present Value), Net Benefit/Cost (B/C), IRR (Internal Rate of Return) and Payback Period. The results of the research on the development plan for a tapioca flour processing business are profitable or feasible to run in Aceh Besar District, based on the Net Present Value (NPV) on the Discount Factor (DF) of 14% for an economic life of 15 years of Rp. 6,879,487,975, the Net B/C value is 4.66, the IRR is 88.36%, and the Pay back period (PBP) is 4 years, 9 months, which is less than the project life.